GEOGRAPHICAL INDICATIONS A COMPARATIVE RESEARCH BETWEEN EURPEAN UNION, UNITED STATES AND BRAZIL - Aveni, Alessandro (Revista JRG de Estudos Acadêmicos, 2019)
This paper aims to clarify the interpretations of article 22 of the 1994 TRIPs agreement in different economic blocks. In addition to the quantitative differences in the number of GIs between blocks, one should also note that it is important in the agreements to understand the different interpretations of intellectual property: a) international interpretations of trade treaties linked to the World Trade Organization (WTO) and intellectual property linked to World Intellectual Property Organization (WIPO), b) interpretations of the national legal framework as, for example, explained in the text by Brazil. The work compares interpretations of the European, United States and Brazil. The most relevant result of this international comparison is to understand that in GI certification the geographical name and sales-related production for consumers in the three blocks have different meanings and are supported by different trading strategies.